Soft, skin-interfaced wireless electrogoniometry systems for continuous monitoring of finger and wrist joints - Hee-Sup Shin; Jihye Kim; Nicholas Fadell; Logan B. Pewitt; Yusuf Shaaban; Claire Liu; Min-Seung Jo; Josif Bozovic; Andreas Tzavelis; Minsu Park; Kelly Koogler; Jin-Tae Kim; et al. (Nature Communications)
Abstract Continuous kinematic biofeedback during exercise interventions can lead to improved therapeutic outcomes in hand and wrist rehabilitation. Conventional methods for measuring joint kinematics typically allow only static measurements performed by specially trained therapists. This paper introduces skin-conformal, wearable wireless systems designed to continuously and accurately capture the angles of target joints, specifically in hand and wrist. Supported by a computer vision-based calibration protocol run on a smart device, these magnetometer-based standalone systems provide patients and clinicians with continuous, real-time data on joint angles and ranges of motion through an intuitive graphical interface. Human trials in healthy volunteers demonstrate the accuracy and precision of the electrogoniometry system, as well as its compatibility with simulated hand therapy. We have also demonstrated the electrogoniometry system is suitable for tracking complex and rapid movements and for deployment during occupational tasks where it could serve as a biofeedback device to warn against excessive and clinically contraindicated motion.